1996
DOI: 10.1128/jcm.34.11.2645-2649.1996
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex PCR-based assay for detection of Bordetella pertussis in nasopharyngeal swab specimens

Abstract: A multiplex PCR-based assay was developed for the detection of Bordetella pertussis in nasopharyngeal swab specimens. The assay simultaneously amplified two separate DNA targets (153 and 203 bp) within a B. pertussis repetitive element and a 438-bp target within the ␤-actin gene of human DNA (PCR amplification control). PCR products were detected by a sensitive and specific liquid hybridization gel retardation assay. A total of 496 paired nasopharyngeal swab specimens were tested by both the PCR-based assay an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
1
1

Year Published

1999
1999
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 20 publications
0
10
1
1
Order By: Relevance
“…PCR has repeatedly been shown to be more sensitive than culture and DFA for the detection of B. pertussis (4, 7-11, 13-15, 23, 24, 26, 27, 29). However, resolution of discrepant test results and assessment of the clinical performance of PCR have been carried out infrequently (13,26,29). The PCR test described in this study was shown to have excellent analytical sensitivity (Ͻ1 cell per PCR).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…PCR has repeatedly been shown to be more sensitive than culture and DFA for the detection of B. pertussis (4, 7-11, 13-15, 23, 24, 26, 27, 29). However, resolution of discrepant test results and assessment of the clinical performance of PCR have been carried out infrequently (13,26,29). The PCR test described in this study was shown to have excellent analytical sensitivity (Ͻ1 cell per PCR).…”
Section: Discussionmentioning
confidence: 92%
“…Accurate laboratory identification of B. pertussis infections remains problematic. Culture, long considered the "gold-standard" diagnostic method, is highly specific, but sensitivity can be affected by a number of factors, including patient age, immunization status, antibiotic treatment and duration of symptoms prior to specimen collection, and specimen transport conditions (28,29). The turnaround time for culture is typically 7 to 10 days for a negative specimen.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Suspensions of nasopharyngeal secretions were obtained from a collection maintained by the Pediatric Molec-ular Microbiology Laboratory at Children's Hospital of Pittsburgh (PA). The secretions were collected with Dacron swabs and suspended in 500 l of saline, and the suspensions were stored at Ϫ80°C as single-use aliquots (i.e., 100 l) until needed (25). The swab specimens had been obtained as part of routine care of pediatric patients who were evaluated for pertussis between February and May 2005.…”
Section: Methodsmentioning
confidence: 99%
“…One rapid screening method is based on the detection of calmodulin-dependent adenylate cyclase (AC)-hemolysin by an assay with an alginate swab specimen from the nasopharynx (7). Multitarget PCR-based assays (13,26) are sensitive and more efficient than culture, but nasopharyngeal sampling with Dacron swabs is required. No comparison of the results of the AC test and PCR-based diagnosis has been reported to date.…”
mentioning
confidence: 99%